Drainage Water Salt Load Variations Related to the Salinity and Leaching Ratios of Irrigation Water - Engin Yurtseven; Hasan Sabri Öztürk; Müslime Sevba Çolak; Ahmet Öztürk (Journal of Agricultural Sciences)
Solubility of salts and leaching fractions have different effects on drainage water quality. Knowing the quality of drainage water is extremely important in terms of environmental factors and quality of water resources for the reason that this water is transferred to various sources. In this study, were studied the changes of drainage water salinity and salt load under lyzimeter (soil columns) conditions using different irrigation water salinity and with different leaching fractions. The study was carried out with sunflower in PVC soil columns with 40 cm diameter and 115 cm length with 3 different irrigations and 5 irrigation waters with different salinity level. The three irrigation treatments were 75%, 115% and 135% of the required irrigation water. The irrigation water salinities were 0.25 dS m-1 as control treatment, 1.5 and 3.0 dS m-1 with NaCl+CaCl2 salts and 1.5 and 3.0 dS m-1 with NaCl+CaSO4 salts as saline treatments. In this study investigated drainage water quality variations and salt load with irrigation water and some individual ions load and their leaching by drainage water as well. Drainage water salinities variated with both irrigation water salinity and leaching fractions. It was higher under the effect of soluble salts and with the 15% leaching fraction. However, salt load was higher at 35% leaching fractions level. When discuss the individual ions; while Cl-,  (CO3-2+HCO3-) and Ca+2 were accumulated in the soil profile, SO4-2, Na+ ve Mg+2 were leaced from the profile, and all these ions variated by interaction for irrigation waters, and by leaching fractions for the drainage water.